Attractive urban lighting as a new destination branding - Rizky Amalia Achsani; Kurniati Ornam; Hanson Endra Kusuma; Surjamanto Wonorahardjo; Sugeng Triyadi (ARTEKS : Jurnal Teknik Arsitektur, 2022)
In recent decades places that use attractive urban lighting to attract visitors have emerged. This shows a shift in lighting, giving the impression of a place, nocturnal image, and attracting attention. The purpose of this paper is to explore places, activities, and impressions of attractive urban lighting to see its potential in improving city visuals at night. The data was collected through an online questionnaire distributed by a non-random snowball sampling method from 126 respondents. The analysis was carried out in stages, starting with content analysis and continued with correspondence analysis and hierarchical clustering. The results showed that places with attractive urban lighting could be grouped into seven categories of place, ten categories of activity, six categories of impression. Three models are formed from these themes, namely cognitive image, unique images, and affective image, which will form an overall image of attractive urban lighting as the new destination branding.